2005
DOI: 10.1016/j.bbamem.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cations affect chain mobility and aggregate structure of lipopolysaccharide from Salmonella minnesota reflected in a decrease of its biological activity

Abstract: The physicochemical properties and biological activities of rough mutant lipopolysaccharides Re (LPS Re) as preformed divalent cation (Mg2+, Ca2+, Ba2+) salt form or as natural or triethylamine (Ten+)-salt form under the influence of externally added divalent cations were investigated using complementary methods: Differential scanning calorimetry (DSC) and Fourier-transform infrared spectroscopic (FT-IR) measurements for the beta <--> alpha gel to liquid crystalline phase behaviour of the acyl chains of LPS, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
78
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 35 publications
14
78
0
Order By: Relevance
“…A similar trend is observed in phospholipid membrane systems, where the addition of lipids containing ChoP reduce membrane permeability and the T m [47]. In DSC experiments using LPS isolated from Salmonella minnesota , it was found that mutants with reduced oligosaccharide extensions had a lower T m , demonstrating that changes to the oligosaccharide, in addition to lipid A alterations, can affect the phase transition temperature [51], [73].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A similar trend is observed in phospholipid membrane systems, where the addition of lipids containing ChoP reduce membrane permeability and the T m [47]. In DSC experiments using LPS isolated from Salmonella minnesota , it was found that mutants with reduced oligosaccharide extensions had a lower T m , demonstrating that changes to the oligosaccharide, in addition to lipid A alterations, can affect the phase transition temperature [51], [73].…”
Section: Discussionsupporting
confidence: 65%
“…Increasing the Mg 2+ concentration (up to 50 mM) resulted in reduced antibody binding to the ChoP− phase variant of H233 (Figure 8E). These results demonstrate that excess Mg 2+ , which increases the stability of the outer membrane [49][51], can correct for the difference in antibody binding between ChoP+ and ChoP− variants. Together, these data indicate that ChoP expression alters the physical properties of the outer membrane, and that these effects correlate with the reduction of antibody binding in ChoP+ phase variants.…”
Section: Resultsmentioning
confidence: 67%
“…The DSC data were analyzed using the Origin software. The phase transition enthalpy was obtained by integrating the area under the heat capacity curve [16].…”
Section: Differential Scanning Calorimetry (Dsc) On Dmpc and Dmpementioning
confidence: 99%
“…Indeed, Waldron et al (2003) reported that experimental endotoxemia was associated with hypocalcemia. It is not clear whether lowering of plasma calcium occurs because calcium binds endotoxin to neutralize its biological effects as suggested by Garidel et al (2005) or because calcium mobilization is impaired during administration of endotoxin (Zaloga et al, 1992). This remains to be clarified in the future.…”
Section: Milk Fevermentioning
confidence: 99%